Epigenetic Modification 6‐Methyladenosine Can Impact the Potency and Specificity of siRNA. (23rd October 2020) - Rydzik, Anna M.; Gottschling, Dirk; Simon, Eric; Skronska‐Wasek, Wioletta; Rippmann, Jörg F.; Riether, Doris
Abstract: The introduction of N 6‐methyladenosine (m6 A) into siRNA targeting Factor VII impacts its potency in cells and has a significant influence on the selectivity of siRNA, including reduced off‐targeting. These effects are dependent on the position of m6 A in the siRNA duplex, with some of the sequences identified as more potent and/or selective than their non‐methylated counterpart. These findings broaden the repertoire of available chemical modifications for siRNA therapeutics and imply potential regulatory role of N 6‐methyladenosine in the RNAi pathways. Abstract : Depending on where you put Me : The introduction of N 6‐methyladenosine into siRNA impacts its potency in cells in a position‐dependent manner and has significant influence on the selectivity of siRNA, including reduced off‐targeting. These findings broaden the repertoire of available chemical modifications for siRNA therapeutics and imply potential regulatory role of N 6‐methyladenosine in the RNAi pathways.